2021
DOI: 10.3390/su13063437
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Vacuum Impregnation as a Strategy for the Management of Potato By-Products

Abstract: One of the most important problems of the modern world is food wastage. The issue occurs at every stage of the food chain, requiring new sustainable production and processing technologies. The processing of production waste and making it a wholesome ingredient may be a good opportunity to promote more sustainable development. This study analyzes the process of enrichment of model by-product (irregular potatoes cubes) with a functional compound (ascorbic acid) through vacuum impregnation, with two experiments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…
Fig. 1 Schematic of the impregnation apparatus [24] . 1 & 4 - valves, 2 - PT100 temperature probe, 3 - vacuum gauge, 5 - lid, 6 - vacuum chamber, 7 - water jacket, 8 - vacuum pump, 9 - ultrasonic transducers.
…”
Section: Study Methodologymentioning
confidence: 99%
“…
Fig. 1 Schematic of the impregnation apparatus [24] . 1 & 4 - valves, 2 - PT100 temperature probe, 3 - vacuum gauge, 5 - lid, 6 - vacuum chamber, 7 - water jacket, 8 - vacuum pump, 9 - ultrasonic transducers.
…”
Section: Study Methodologymentioning
confidence: 99%
“…
Fig. 1 Scheme of impregnation apparatus [17] . 1,4 – valves; 2 – PT100 temperature probe; 3 – vacuum gauge; 5 – lid, 6 – vacuum chamber; 7 – water jacket; 8 – vacuum pump; 9 – ultrasonic transducers.
…”
Section: Methodology Of the Studymentioning
confidence: 99%
“…Potential benefits associated with the use of ultrasonics in potato cultivation may include increased potato yield, better plant resistance to environmental stresses, reduced pesticide usage, and improved crop quality. In terms of crop quality improvement, Mierzwa et al [28] have reported on the benefits of ultrasonically assisted vacuum impregnation for drying potato cubes, originally considered as valueless production waste. According to these authors, this approach allows for the transformation of valueless production waste into a valuable product with a high content of impregnating compounds (in this case, ascorbic acid).…”
Section: The Influence Of Ultrasound Technology On Plant Growth and S...mentioning
confidence: 99%
“…Therefore, selecting the appropriate variety for cultivation should take into account local environmental conditions, production goals, and the availability of agricultural technologies and plant protection. It is also important to consider the preferences of producers to understand their preferences regarding selected varieties in combination with ultrasound technology [28].…”
Section: Variability Of Varieties and Their Drought Tolerancementioning
confidence: 99%